Investigating the feasibility of a new testing method for GFRP/polymer foam sandwich composites used in railway passenger vehicles. (1st February 2020) - Önder, Asım; Robinson, Mark
Abstract: This paper investigates the feasibility and validity of a recently proposed testing method when applied to foam core sandwich composites to determine the impact resistance of train car body shells. The published method proved itself useful when applied to monolithic fibre reinforced plastic laminates, however, further analysis is required if sandwich composites are used due to the subtle differences compared to monolithic laminates. It is especially important for the front nose section of high-speed trains as these car body parts can be subjected to ballast flight at high impact velocities. Due to the aerodynamic design aspects, front nose sections generally incorporate complex 3D geometries, and sandwich composite materials are advantageous in this respect due to the ease of manufacturing of complex 3D shapes. Quasi-static punch tests (QSPT) were performed on E-glass fibre/epoxy resin/PET foam core sandwich plates. Numerical finite element model (FEM) was developed and validated with experiments in terms of penetration resistance and structural damage. Numerical model was used to investigate three railway impact related standards and high-velocity impact parameters (energy transfer, contact force, projectile velocity) were analysed for each case. Additionally, the foreseeable contribution of this work to the railway industry was given from multiple aspects.